2020
DOI: 10.6023/cjoc201912007
|View full text |Cite
|
Sign up to set email alerts
|

Triazine Derivative for Fluorescence Sensing of Zr4+, Fe3+ Ions and Acetone

Abstract: 2,2',2''- (1,3,4,tribenzoic acid (L, H 3 TATIB) fluorescence response chemosensor has been synthesized by one pot reaction and its fluorescent behaviors to transition metal ions were systematically investigated. The experimental results show that the recognition of Zr 4+ and Fe 3+ is realized in N,N-dimethylformamide (DMF) aqueous solution; The compound L can effectively detect acetone in organic solvent. The detection limits of Zr 4+ and Fe 3+ are 3.60×10 -6 and 1.33×10 -6 mol/L, respectively. It was prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In previous studies, detection of Zr 4+ has been mainly achieved through inductive coupled plasma/glow discharge mass spectrometry (ICP-MS, GC–MS) , and reversed phase liquid chromatography (RP-LC). , In spite of their high sensitivity, these methods require sophisticated instrumentation with high cost and utility of toxic organic solvents, limiting their practical applications. Few spectrophotometric , and fluorescent approaches were also employed for Zr 4+ detection. Despite of their fast analysis and easy operations, those methods exhibited poor sensitivity and needed incorporation of high-cost DNA recognition probes …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, detection of Zr 4+ has been mainly achieved through inductive coupled plasma/glow discharge mass spectrometry (ICP-MS, GC–MS) , and reversed phase liquid chromatography (RP-LC). , In spite of their high sensitivity, these methods require sophisticated instrumentation with high cost and utility of toxic organic solvents, limiting their practical applications. Few spectrophotometric , and fluorescent approaches were also employed for Zr 4+ detection. Despite of their fast analysis and easy operations, those methods exhibited poor sensitivity and needed incorporation of high-cost DNA recognition probes …”
Section: Resultsmentioning
confidence: 99%
“…36,37 In spite of their high sensitivity, these methods require sophisticated instrumentation with high cost and utility of toxic organic solvents, limiting their practical applications. Few spectrophotometric 38,39 and fluorescent approaches 40 were also employed for Zr 4+ detection. Despite of their fast analysis and easy operations, those methods exhibited poor sensitivity and needed incorporation of high-cost DNA recognition probes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this work, a new complex, Al-MOF[L=2,2',2'-([1, 3, 5]-triazine-2,4,6-triimino)tribenzoic acid] has been prepared by reaction of L with Al(III) salt in DMF solution. The ligand L is synthesied by 'one pot' reaction in glacial acetic acid solution according to the previous work [34]. The Al-MOF was investigated for multiple fluorescence response to Fe 3+ , Sr 2+ , SiO 3 2− ions and toluene, especially it is first reported that the fluorescence intensity of Al-MOF is enhanced when Fe 3+ , Sr 2+ and SiO 3 2− ions are added in DMF/H 2 O solution, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The ligand L is synthesized by "one pot"' reaction in glacial acetic acid solution, and the complexation ratio of ligand L to Zr 4 + was also determined according to the previous work. [64] The Zr-MOF was investigated for the fluorescence response to the metal cations, anions and organic small molecules, especially it is reported that Zr-MOF can detect CCl 4 and xylene in DMF solution.…”
Section: Introductionmentioning
confidence: 99%